Preparation method and application of NiCo-based Prussian blue analogue electro-catalytic material

NiCo-PBAs/NF catalytic material is prepared by co-precipitation on a foam nickel substrate to form a three-dimensional nanocube structure, which solves the problems of slow OER and sulfur substance poisoning in traditional electrochemical water decomposition, and achieves efficient hydrogen production and sulfur recovery. Reduces electricity consumption and costs.

CN119265605APending Publication Date: 2025-01-07TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411278948.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The slow oxygen precipitation reaction (OER) in traditional electrochemical water decomposition hinders the practical application of hydrogen production, and the chemical adsorption and etching of hydrogen sulfide lead to strong poisoning effects of sulfur substances on metal electrocatalysts, increasing the preparation of high-efficiency catalysts. cost.

Method used

NiCo pyprusian blue analog catalytic material (NiCo-PBAs/NF) was prepared on foam nickel substrate by co-precipitation method to form a unique three-dimensional nanocube structure as a dual-purpose sulfur oxidation reaction (SOR) and hydrogen evolution reaction (HER) Functional catalyst, reducing reaction potential.

Benefits of technology

The potential required for the reaction is significantly reduced, the catalytic activity and stability are improved, and good reactivity in the electrocatalytic reaction of cathode and anode is achieved, and the power consumption of overall hydrogen production is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265605A_ABST
    Figure CN119265605A_ABST
Patent Text Reader

Abstract

The invention aims to provide a preparation method and application of a NiCo-based Prussian blue analogue electro-catalytic material, and belongs to the technical field of nano materials and electrochemical catalysts.According to the Prussian blue analogue NiCo-PBAs / NF catalytic material prepared through a simple coprecipitation method, PBAs nano cube particles are stacked on an NF substrate to form a unique three-dimensional structure, and the Prussian blue analogue NiCo-PBAs / NF catalytic material can be used for preparing the NiCo-based Prussian blue analogue electro-catalytic material. The unique self-supporting nanocube structure is beneficial to mass transfer between active components and a substrate, electrochemical active sites are greatly improved, and chemical reaction energy barriers are reduced. The material can be used as a catalyst for SOR and HER reaction, is applied to hydrogen production by water electrolysis and industrial wastewater and waste gas treatment, and has very high catalytic activity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano materials and electrochemical catalysis, and specifically relates to a preparation method and application of a NiCo-based Prussian blue analogue electrocatalytic material. Background Art

[0002] Hydrogen produced by electrochemical water splitting is considered to be one of the most promising chemicals to replace fossil fuels and provide clean renewable energy in the future. However, the slow oxygen evolution reaction (OER) in conventional electrochemical water splitting has seriously hindered its practical application. Using more easily oxidized molecules such as glucose, biomass-derived alcohols and urine, waste gas, etc. as cathode reactions to replace OER is a promising way to reduce the overall energy consumption of hydrogen production and obtain additional products at the same time. Hydrogen sulfide (H2S) is one of the millions of tons of toxic pollutants emitted from refineries and natural gas extraction industries every year. By removing and utilizing this hazardous waste by electrochemical methods, hydrogen production and sulfur recovery can be achieved at the cathode and anode, respectively, which is more economical and environmentally friendly than the current industrial Claus process that only achieves sulfur recovery.

[0003] When the oxygen evolution reaction (OER) is replaced by the sulfide oxidation reaction (SOR), the theoretical voltage of hydrogen production can be significantly reduced from 1.23V to 0.17V, thus saving 86% of electrical energy. However, research exploring efficient hydrogen production systems based on SOR is quite limited. One main reason is that sulfur substances have a strong poisoning effect on metal electrocatalysts due to the chemical adsorption and etching of sulfur elements. Currently, most reports have grown coating materials on metal nanoparticles that can protect metal catalysts from harsh sulfur poisoning, thereby improving the corrosion resistance of the catalyst and achieving stable electrocatalytic SOR performance. However, catalyst preparation usually requires high-temperature pyrolysis or template etching processes, which will lead to increased costs. Therefore, it remains a huge challenge to construct a cheap, anti-poisoning and high-performance electrode for large-scale SOR-assisted hydrogen production. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a NiCo-based Prussian blue analogue electrocatalytic material and its application. The Prussian blue analogue NiCo-PBAs / NF catalytic material prepared by a simple coprecipitation method, the PBAs nanocube particles are stacked on the NF substrate to form a unique three-dimensional structure, this unique self-supporting nanocube structure is conducive to mass transfer between the active component and the substrate, greatly improves the electrochemical active sites, and reduces the chemical reaction energy barrier. The material can be used as a catalyst for SOR and HER reactions, applied to water electrolysis to produce hydrogen and industrial wastewater and waste gas treatment, and has high catalytic activity and stability.

[0005] The present invention adopts the following technical solution: A method for preparing a NiCo-based Prussian blue analog electrocatalytic material comprises the following steps: In the first step, potassium ferrocyanide (K3[Fe(CN)6]) was dissolved in deionized water and stirred continuously, which was marked as solution A. In the second step, nickel nitrate (Ni(NO3)2·6H2O), cobalt nitrate (Co(NO3)2·6H2O), and sodium citrate (Na3C6H5O7·2H2O) were dissolved in deionized water and stirred continuously, which was marked as solution B. The third step is to slowly add solution B into solution A, stir thoroughly, put the cleaned nickel foam substrate into the solution, and let it stand for 24 hours; In the fourth step, the substrate obtained in the third step is cleaned with deionized water and ethanol respectively, and then placed in an oven for drying to obtain a NiCo-PBAs / NF catalyst supported on nickel foam.

[0006] Furthermore, the concentration of potassium ferrocyanide in the solution A in the first step is 0.01-0.6 mol / L.

[0007] Furthermore, in the second step, the concentrations of nickel nitrate and cobalt nitrate in the solution B are 0.01-0.8 mol / L in total; and the concentration of sodium citrate is 0.045-0.5 mol / L.

[0008] Furthermore, the amount of nickel nitrate is 0.5-20 mmol; the amount of cobalt nitrate is 0.5-20 mmol.

[0009] Furthermore, the stirring time in the third step is 10 to 20 minutes, until the color turns brown.

[0010] Furthermore, in the third step, the nickel foam is cleaned with hydrochloric acid solution, deionized water, and ethanol ultrasonic treatment in sequence and then dried.

[0011] A NiCo-based Prussian blue analogue electrocatalytic material is applied as a bifunctional catalyst in SOR and HER.

[0012] The beneficial effects of the present invention are as follows: The present invention directly prepares a Prussian blue analogue catalyst (NiCo-PBAs / NF) on nickel foam by a coprecipitation method, wherein a large number of PBAs nanocubes are accumulated on NF to form a unique three-dimensional structure, and the unique self-supporting nanocube structure is conducive to promoting mass transfer between active components and substrates, and maximizing electrochemical active sites. The material can be used as a bifunctional catalyst in SOR and HER, and SOR and HER are coupled by an H-type electrolytic cell, which proves that the potential required for the reaction can be significantly reduced after SOR replaces OER. Therefore, NiCo-PBAs / NF, as a bifunctional catalyst, has good reaction activity in both cathode and anode electrocatalytic reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a SEM image of the NiCo-PBAs / NF catalytic material of Example 1 of the present invention; Figure 2 The XRD graph (a) and Raman graph (b) of the NiCo-PBAs / NF catalytic material of Example 1 of the present invention; Figure 3 The linear sweep voltammetric curve (a), Tafel slope curve (b), electrochemical impedance curve (c) and stability test (d) of the hydrogen evolution reaction performance of the NiCo-PBAs / NF catalytic material of Example 1 of the present invention under the conditions of 1 mol / L NaOH and 5 mV / s scan rate; Figure 4 The linear sweep voltammetric curve (a), Tafel slope curve (b), sulfur oxidation reaction and oxygen evolution reaction comparison curve (c) and stability test curve (d) of the NiCo-PBAs / NF catalytic material of Example 1 of the present invention in 1 mol / L NaOH+Na2S electrolyte at a sweep rate of 5 mV / s are shown; Figure 5 It is the full hydrolysis performance of the NiCo-PBAs / NF catalytic material of Example 1 of the present invention, including a full hydrolysis schematic diagram (a), full hydrolysis performance (b), absorption wavelength of the reaction process product (c), and XRD diagram of the reaction product (d). DETAILED DESCRIPTION

[0014] The technical solution of the present invention is described below with specific embodiments, but the protection content of the present invention is not limited to the following embodiments.

[0015] A method for preparing a NiCo-based Prussian blue analog electrocatalytic material comprises the following steps: S1. Dissolve K3[Fe(CN)6] in deionized water and keep stirring, which is called solution A. S2, dissolve Ni(NO3)2·6H2O, Co(NO3)2·6H2O, and Na3C6H5O7·2H2O in deionized water and stir continuously, which is referred to as solution B; S3, slowly add solution B to solution A and continue stirring until the color of the mixed solution turns brown, put the cleaned nickel foam substrate into the mixed solution and let it stand for 24 hours; The nickel foam was placed in 1 mol / L dilute hydrochloric acid, deionized water, and ethanol solution for 15 min each, and then placed in a vacuum drying oven for drying. S4. The obtained substrate is cleaned with deionized water and ethanol respectively, and then placed in an oven for drying to obtain a NiCo-PBAs / NF catalyst supported on nickel foam.

[0016] Optionally, in step S1, the amount of K3[Fe(CN)6] is in the range of 0.5-30 mmol, and the volume of deionized water is in the range of 40-80 mL.

[0017] Optionally, in step S2, the amount of Ni(NO3)2·6H2O is in the range of 0.5~20 mmol, the amount of Co(NO3)2·6H2O is in the range of 0.5~20 mmol, the amount of Na3C6H5O7·2H2O is in the range of 0.5~25 mmol, and the volume of deionized water is in the range of 40~80 mL.

[0018] Example 1 The method for preparing NiCo-PBAs / NF catalytic material comprises the following steps: 1) Dissolve 1 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 1mmol nickel nitrate Ni(NO3)2·6H2O, 0.5mmol cobalt nitrate (Co(NO3)2·6H2O), and 2.225mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0019] Taking the NiCo-PBAs / NF catalyst in this embodiment as an example, its morphological characteristics are as follows Figure 1 As shown in the figure, a large number of NiCo-PBAs nanocubes can be observed to accumulate on the NF substrate to form a unique three-dimensional structure. This unique self-supporting nanocube structure is conducive to promoting the adhesion and mass transfer between the active components and the substrate, and can maximize the electrochemical active sites. Its phase structure is determined by the X-ray diffraction spectrum. Figure 2 As shown in the figure, the XRD of NiCo-PBAs / NF belongs to KNi[Fe(CN)6] (PDF#04-0850). With the incorporation of Co, the diffraction peak of PBAs shifts slightly to the right, proving that Co ions with a small ionic radius are successfully incorporated into the NiFe-PBAs lattice. Combined with the Raman graph, it can be seen that with the increase in the amount of Co ion incorporation, the crystallinity of PBAs gradually decreases. This is because the addition of Co ions causes structural disorder and micro-strain of the internal NiFe-PBAs lattice, which further affects the growth of grains and leads to a decrease in peak intensity.

[0020] In this embodiment, the electrocatalytic performance of the NiCo-PBAs / NF catalytic material was measured by an electrochemical workstation (CS3104). In the electrocatalytic test, a NiCo-PBAs / NF electrode, a graphite rod electrode and a mercuric oxide electrode were used as the working electrode, the counter electrode and the reference electrode, respectively, to form a standard three-electrode system.

[0021] Taking the NiCo-PBAs / NF catalytic material as the working electrode in this embodiment, the HER performance diagram is as follows: Figure 3 , NiCo-PBAs / NF catalytic material at 10 mA cm -2 and 100mA cm -2 The overpotentials at current density are 97 mV and 337 mV, respectively, which are much smaller than those of NiFe-PBAs / NF (197 and 495 mV) and NiCo-LDH / NF (221 and 512 mV). The Tafel slope curve is usually used to evaluate the kinetic rate of catalytic reactions. The Tafel slope of NiCo-PBAs / NF catalytic material is 171 mV dec. −1 , which is much lower than NiCo-LDH / NF (274 mV dec −1 ) and NiFe-PBAs / NF (200 mV dec −1), which indicates that it has relatively fast HER reaction kinetics. In the electrochemical impedance diagram, NiCo-PBAs / NF shows smaller liquid junction resistance and Rct, indicating that NiCo-PBAs / NF has stronger charge transfer ability. At the same time, due to the large number of bubbles generated in the hydrogen evolution reaction, this has a certain impact on the electrode, so long-term hydrogen evolution reaction is also a necessary test for electrode performance. It can be seen from the stability test diagram that NiCo-PBAs / NF can be maintained within 10h, proving its excellent stability.

[0022] SOR performance Figure 4 As shown in the figure, for the SOR catalytic reaction, in 1 mol / L Na2S + NaOH electrolyte, the NiCo-PBAs / NF catalysts -2 and 100mA cm -2 The oxidation potentials of the catalysts were 0.32 and 0.45 V vs. RHE at an anodic current density of 1.3 Å, which were significantly better than those of NiFe-PBAs / NF and NiCo-LDH / NF catalysts. This result indicates that the Co-doped Prussian blue structure greatly improves the SOR activity. The Tafel slope of the NiCo-PBAs / NF catalyst is 8.6 mV dec −1 , which is much lower than FeFe-PBAs / NF (12.8 mV dec −1 ) and NiFe-PBAs / NF (10.68 mV dec −1 ), which indicates that the reaction kinetics of sulfur oxidation reaction of NiCo-PBAs / NF catalytic material is faster. Compared with the oxygen evolution reaction, NiCo-PBAs / NF catalyst reaches a current density of 10mA cm -2 The potential at 1.33 V was significantly reduced, which confirmed that the sulfur oxidation reaction was thermodynamically more advantageous than the oxygen evolution reaction. In addition, after the long-term SOR stability test at an applied voltage of 0.42 V vs. RHE, the NiCo-PBAs / NF catalyst showed good SOR stability.

[0023] Figure 5 This is a performance test diagram of the full water splitting experiment of a two-electrode water electrolyzer using NiCo-PBAs / NF as both anode and cathode. In the image of the cathode area, a large number of H2 bubbles can be observed to overflow rapidly from the cathode electrode. At the same time, the electrolyte is dark yellow, indicating that polysulfides gradually accumulate during sulfur oxidation. The LSV curve shows that at the same voltage, the SOR / HER electrolyzer exhibits a higher current density than the traditional OER / HER electrolyzer. For the traditional water electrolysis system, the three-electrode system using NiCo-PBAs / NF electrodes reaches 10mA cm -2The current density requires a higher voltage of 1.58 V vs. RHE; while the NiCo-PBAs / NF electrode assembled in the SOR / HER electrolysis system only requires 0.33 V vs. RHE.

[0024] Example 2 1) Dissolve 3 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 3mmol nickel nitrate Ni(NO3)2·6H2O, 3mmol cobalt nitrate (Co(NO3)2·6H2O), and 2.225mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0025] Example 3 1) Dissolve 6 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 3mmol nickel nitrate Ni(NO3)2·6H2O, 3mmol cobalt nitrate (Co(NO3)2·6H2O), and 5mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0026] Example 4 1) Dissolve 10 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 10mmol nickel nitrate Ni(NO3)2·6H2O, 20mmol cobalt nitrate (Co(NO3)2·6H2O), and 10mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0027] Example 5 1) Dissolve 12.5 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 25mmol nickel nitrate Ni(NO3)2·6H2O, 12.5mmol cobalt nitrate (Co(NO3)2·6H2O), and 10mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0028] Example 6 1) Dissolve 12.5 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 12.5mmol nickel nitrate Ni(NO3)2·6H2O, 12.5mmol cobalt nitrate (Co(NO3)2·6H2O), and 10mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0029] Example 7 1) Dissolve 12.5 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 12.5mmol nickel nitrate Ni(NO3)2·6H2O, 25mmol cobalt nitrate (Co(NO3)2·6H2O), and 10mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0030] Example 8 1) Dissolve 20 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 20mmol nickel nitrate Ni(NO3)2·6H2O, 20mmol cobalt nitrate (Co(NO3)2·6H2O), and 25mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

[0031] Example 9 1) Dissolve 20 mmol potassium ferrocyanide (K3[Fe(CN)6]) in deionized water and continue stirring until the solution turns light yellow; 2) Dissolve 20mmol nickel nitrate Ni(NO3)2·6H2O, 10mmol cobalt nitrate (Co(NO3)2·6H2O), and 25mmol Na3C6H5O7·2H2O in deionized water and keep stirring; 3) Slowly add the solution in step 2) into the solution in step 1) and continue stirring until the color of the solution completely turns brown; 4) Adding nickel foam to the mixed solution obtained in step 3) and leaving it to stand for 24 hours; 5) The nickel foam obtained in step 4) was rinsed with deionized water and ethanol respectively, and then dried in a vacuum drying oven at 70° C. to obtain a NiCo-PBAs / NF catalyst supported on a nickel foam substrate.

Claims

1. A method for preparing a NiCo-based Prussian blue analog electrocatalytic material, characterized in that: The steps include: In the first step, potassium ferrocyanide is dissolved in deionized water and stirred continuously, which is marked as solution A. In the second step, nickel nitrate, cobalt nitrate and sodium citrate are dissolved in deionized water and stirred continuously, which is marked as solution B; The third step is to slowly add solution B into solution A, stir thoroughly, put the cleaned nickel foam substrate into the solution, and let it stand for 24 hours; In the fourth step, the substrate obtained in the third step is cleaned with deionized water and ethanol respectively, and then placed in an oven for drying to obtain a NiCo-PBAs / NF catalyst supported on nickel foam.

2. The method for preparing a NiCo-based Prussian blue analog electrocatalytic material according to claim 1, characterized in that: The concentration of potassium ferrocyanide in solution A in the first step is 0.01-0.6 mol / L.

3. The method for preparing a NiCo-based Prussian blue analog electrocatalytic material according to claim 1, characterized in that: In the second step, the concentrations of nickel nitrate and cobalt nitrate in the solution B are 0.01-0.8 mol / L in total; the concentration of sodium citrate is 0.045-0.5 mol / L.

4. The method for preparing a NiCo-based Prussian blue analog electrocatalytic material according to claim 1, characterized in that: The amount of nickel nitrate is 0.5-20 mmol; the amount of cobalt nitrate is 0.5-20 mmol.

5. The method for preparing a NiCo-based Prussian blue analog electrocatalytic material according to claim 1, characterized in that: The stirring time in the third step is 10 to 20 minutes, until the color turns brown.

6. The method for preparing a NiCo-based Prussian blue analog electrocatalytic material according to claim 1, characterized in that: In the third step, the nickel foam is cleaned by using hydrochloric acid solution, deionized water, ethanol ultrasonic treatment in sequence and then dried.

7. A NiCo-based Prussian blue analogue electrocatalytic material prepared by the preparation method according to any one of claims 1 to 6, which is used as a bifunctional catalyst in SOR and HER.